Comparative Analysis of User Experience in SeaBank and Bank Jago using the User Experience Questionnaire - Shinta Dwina Hendriyani; Arny Lattu; Moneyta Dholah Rosita (SISTEMASI, 2026)
The rapid development of information technology has driven a shift in banking services from conventional systems toward more efficient and flexible digital platforms. Generation Z, as digital natives, has become the primary user group of these services due to their strong preference for convenience and ease in financial transactions. According to data from the Google Play Store, the SeaBank and Bank Jago applications have each been downloaded more than 10 million times, indicating strong public interest in digital banking services. Despite having a similar number of downloads, there is a notable difference in user ratings: SeaBank has received a rating of 4.9 out of 5, while Bank Jago has obtained a rating of 4.5. However, research that directly compares user experience across popular digital banking platforms in Indonesia remains limited. Therefore, this study contributes empirical insights into the factors influencing Generation Z’s satisfaction when using digital banking services. This study aims to analyze and compare the user experience of the SeaBank and Bank Jago applications using the User Experience Questionnaire (UEQ) method. Research data were collected through questionnaires distributed using purposive sampling, targeting Generation Z respondents aged 17–28 years. The collected data were analyzed using the UEQ Data Analysis Tool. The results indicate that both applications received positive evaluations from respondents. Bank Jago outperformed SeaBank in the Attractiveness dimension, reflecting stronger visual and emotional appeal. Meanwhile, SeaBank showed superior performance across the other five dimensions: Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. These findings suggest that SeaBank provides a more efficient, clear, engaging, and innovative user experience compared to Bank Jago.